2019
DOI: 10.12659/msm.913614
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunctions in Obese Women Before and After Bariatric Surgery

Abstract: Background Obesity and associated comorbidities increase the probability of sexual disorders. The present study evaluated sexual satisfaction levels in obese women prior to and following bariatric surgery, utilizing the validated Female Sexual Function Index (FSFI) to also evaluate the sexual satisfaction in obese and non-obese women. Material/Methods 60 obese women (mean initial BMI of 43.7±5.9 kg/m 2 ; mean age of 41.7±10.8 years) were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
1
16
0
2
Order By: Relevance
“…In another study, there was a statistically significant change observed in all subdomains of FSFI, except desire, at the sixth month after surgery 25 . In addition, Pichlerova et al’s study, which compared 60 obese and 60 control patients, showed that the FSFI values increased after bariatric surgery but never reached the values recorded in the control group 26 . Recently, Olivera et al compared sex positions after bariatric surgery and found that the number of sex positions that the couples engaged in increased after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, there was a statistically significant change observed in all subdomains of FSFI, except desire, at the sixth month after surgery 25 . In addition, Pichlerova et al’s study, which compared 60 obese and 60 control patients, showed that the FSFI values increased after bariatric surgery but never reached the values recorded in the control group 26 . Recently, Olivera et al compared sex positions after bariatric surgery and found that the number of sex positions that the couples engaged in increased after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Two follow-up surveys of 60 and 43 women in the Czech Republic and France, respectively, showed amelioration in all FSFI domains 12 months after bariatric surgery, although in the Czech survey it was only significant regarding the desire category [15,23]. Nevertheless, the scores of the surveyed women remained significantly lower than those of the non-obese female reference group [15]. These results concur with those of Janik et al, who found significantly higher FSFI scores in the desire and arousal domains for 153 women 12-18 months after bariatric surgery.…”
Section: Female Sexuality and Sexual Functionmentioning
confidence: 87%
“…In women, this correlation links obesity to disorders of the female cycle and hormone regulation, which are in turn associated with sexual function. Poor self-acceptance of body image, comorbid mental disorders, and difficulties in interpersonal relationships may aggravate the situation [15].…”
Section: Female Sexuality and Sexual Functionmentioning
confidence: 99%
“…Improvement in sex-hormone profile [16] Bariatric surgery and PCOS Weight loss; improvement in insulin resistance; decrease of hirsutism score; restoration of menstrual cycles and/or ovulation [27] Bariatric surgery and anti-Mullerian hormone Normalization of the AMH levels among obese PCOS women [32] Sexual dysfunction in obese women and effects of bariatric surgery Female sexual function resolved after surgical treatment [38]. Weight reduction after bariatric surgery results in reduced sexual dysfunction in female subjects [41] Bariatric surgery and pregnancy Bariatric surgery reduces gestational diabetes, pregnancy induced hypertension and macrosomia and increases risk for SGA and prematurity [47,48] PCOS polycystic ovary syndrome, AMH anti-Mullerian Hormone, SGA Small for Gestational Age pregnancy complications risk are common findings among obese PCOS women [24]. A rise of obesity in PCOS patients may induce the appearance of reproductive and cardiovascular disease [25].…”
Section: Bariatric Surgery and Hypothalamic-pituitary-ovarian Axismentioning
confidence: 99%